(untitled) (Fiep Bulletin - online, 2013)
It discusses the boundaries and possibilities of using the portfolio as an instrument of research and reflection on the Physical Education pedagogical praxis in Preschool education. It is a documental research which analyzed 133 portfolios produced in the Supervised Internship discipline in a Physical Education undergraduate course, between 2002 and 2008. The FIEP BULLETIN Volume 79 - Special Edition - ARTICLE I - 2009 data analysis showed the contribution of this documentation for producing know-how in the previously cited area, clearing some issues related to the theoretical-methodological perspectives of intervention in the Preschool education context. The limits related to the portfolio use as a research instrument are a reflection of the inappropriate conditions of its production, like insufficient space and time to complete it.